Effects of moderate-intensity aerobic exercise on serum BDNF and motor learning in the upper-limb in patients after chronic-stroke: A randomized, controlled feasibility study with embedded health economic evaluation. - Maguire, Clare; Betschart, Martina; Pohl, Johannes; Primani, Francesca; Taeymans, Jan; Hund-Georgiadis, Margret (NeuroRehabilitation, 2023)
BACKGROUND: Brain-derived neurotrophic factor (BDNF) promotes activity-dependent neuroplasticity and is released following aerobic-exercise. OBJECTIVE: Feasibility and efficacy of 1.Moderate-Intensity Cycle-Ergometer-Training (MI-ET) and 2.Low-Intensity Circuit-Training (LI-CT) on BDNF-serum-concentration in chronic-stroke and consequently efficacy of motor-learning in varying BDNF-concentrations (neuroplasticity being the substrate for motor-learning) via upper-limb robotic-training (RT) in both groups. METHODS: Randomised-control feasibility-study. 12-week, 3x/week intervention, 17 chronic-stroke-survivors randomized into: (1) MI-ET&RT or (2) LI-CT&RT. Both groups completed 40 mins MI-ET or LI-CT followed by 40 mins RT. Feasibility outcomes: (1) screening and enrollment-rates, (2) retention-rates, (3) adherence: (i) attendance-rates, (ii) training-duration, (4) adverse events. Primary clinical outcomes: 1. serum-BDNF changes pre-post training (immediate) and pre-training basal-levels over 12-weeks (long-term). 2.upper-limb performance with Action-Research-Arm-Test (ARAT). Additionally, feasibility of an embedded health economic evaluation (HEE) to evaluate health-costs and cost-effectiveness. Outcomes: cost-questionnaire return-rates, cost-of-illness (COI) and Health-Utitility-Index (HUI). RESULTS: 21.5% of eligible and contactable enrolled. 10 randomized to MI-ET and 7 to LI-CT. 85% of training-sessions were completed in MI-ET (306/360) and 76.3% in LI-CT-group (165/216). 12-weeks: Drop-outs MI-ET-10%, LI-CT-43%. Clinical outcomes: No significant changes in immediate or long-term serum-BDNF in either group. Moderate-intensity aerobic-training did not increase serum-BDNF post-stroke. Individual but no group clinically-relevant changes in ARAT-scores. HEE outcomes at 12-weeks: 100% cost-questionnaires returned. Group-costs baseline and after treatment, consistently favouring MI-ET group. COI: (1-year-time-frame): MI-ET 67382 SD (43107) Swiss-Francs and LI-CT 95701(29473) Swiss-Francs. CONCLUSION: The study is feasible with modifications. Future studies should compare high-intensity versus moderate-intensity aerobic-exercise combined with higher dosage arm-training.